2005
DOI: 10.1523/jneurosci.2399-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in PRPF31 Inhibit Pre-mRNA Splicing of Rhodopsin Gene and Cause Apoptosis of Retinal Cells

Abstract: Mutations in human PRPF31 gene have been identified in patients with autosomal dominant retinitis pigmentosa (adRP). To begin to understand mechanisms by which defects in this general splicing factor cause retinal degeneration, we examined the relationship between PRPF31 and pre-mRNA splicing of photoreceptor-specific genes. We used a specific anti-PRPF31 antibody to immunoprecipitate splicing complexes from retinal cells and identified the transcript of rhodopsin gene (RHO) among RNA species associated with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 44 publications
6
51
1
Order By: Relevance
“…It should be pointed out that it remains possible that photoreceptors from different species may have different properties and sensitivities to the presence of mutant Prp31 gene products. Differences in processing of pre-mRNA transcripts have been observed in three separate studies on the rodopsin transcript (Deery et al, 2002;Yuan et al, 2005;Wilkie et al, 2008). The first study reported no effects on the splicing of bovine rodopsin transcripts in the presence of the Prp31 mutant protein in an in vivo splicing assay whereas the latter studies demonstrated dominant effects of Prp31 mutations in affecting splicing efficiency of human rodopsin transcript.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It should be pointed out that it remains possible that photoreceptors from different species may have different properties and sensitivities to the presence of mutant Prp31 gene products. Differences in processing of pre-mRNA transcripts have been observed in three separate studies on the rodopsin transcript (Deery et al, 2002;Yuan et al, 2005;Wilkie et al, 2008). The first study reported no effects on the splicing of bovine rodopsin transcripts in the presence of the Prp31 mutant protein in an in vivo splicing assay whereas the latter studies demonstrated dominant effects of Prp31 mutations in affecting splicing efficiency of human rodopsin transcript.…”
Section: Discussionmentioning
confidence: 94%
“…overexpression of hAD5 mutant form of human Prp31 gene in cultured cells leads to neuronal death and reduced splicing efficiency of a subset of retinal genes (Yuan et al, 2005;Mordes et al, 2007). In our current study, simply expressing hAD5 Prp31 mutant in Drosophila eye did not lead to detectable effect on photoreceptor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies first supported possible explanation 2 and suggested that the removal of intron 3 of RHO is inhibited by the mutated splice factor PRPF31 (Yuan et al, 2005).…”
Section: Retinitis Pigmentosa and Progressive Rod Cone Diseasesmentioning
confidence: 99%
“…(3) Due to specialized requirements (e.g. transcript turnover), photoreceptors depend more strongly than other cell types on efficient splicing.Studies first supported possible explanation 2 and suggested that the removal of intron 3 of RHO is inhibited by the mutated splice factor PRPF31 (Yuan et al, 2005).The authors expressed the mutated PRPF31 to detect the splice defect in RHO.Subsequently, studies suggested that haploinsufficiency is the underlying mechanism for PRPF31 mutations, i.e. the mutated allele is not expressed and the reduced gene The molecular basis of human retinal and vitreoretinal diseases properties of a single RP gene.…”
mentioning
confidence: 99%